Six days of low carbohydrate, not energy availability, alters the iron and immune response to exercise in elite athletes - McKay, A. K. A.; Peeling, P.; Pyne, D. B.; Tee, N.; Whitfield, J.; Sharma, A. P.; Heikura, I. A.; Burke, L. M. (Medicine & Science in Sports & Exercise, 2022)
Purpose To quantify the effects of a short-term (6-d) low carbohydrate (CHO) high fat (LCHF), and low energy availability (LEA) diet on immune, inflammatory, and iron-regulatory responses to exercise in endurance athletes.